Corpos tóxicos: uma etnografia do imaginário e das performatividades de gênero em um terreiro de Umbanda Esotérica de Belo Horizonte (MG) - Giovanna Helena Teixeira da Cruz Silva (2017)
The work aims at analysing questions of gender found in a place of esoteric Umbanda in Belo Horizonte- MG and the comparison between the perception of the umbandistas and the orientations contained in the doctrinal works of this stream of Umbanda, produced by W. W. da Matta and Silva,(1916-1988). The research is composed of the analysis of three works written by Matta and Silva, founder of this stream of Umbanda in Brazil and by ethnographic observations made in the place, in addition to interviews with umbandistas. The analysis of the work stands out theelements related to the gender representations and the action of men and women in the place. Intriguing gender approaches are found in these works, among them, the prohibition of women to lead the places, justified by the fact that their energy is considered passive and that there is an evil substance in their bodies, the menotoxina. From the specific orientations given to women, it was reached the comparison with the way the umbandistas interpreted and updated the ideas from Matta and Silva. Simultaneously, it was possible to analyse the presence of differentbodies, like pomba-gira and their performance in the place and how they affected the ritual organization and the gender perceptions after September, 2015. The conjugation of three identities from the researcher has given a particular characteristic to the research: the umbandista, the feminist and the anthropologist identities. The insertion in the place and the view from the inside have brought elements that may not be noticeable to the external observer. The feminist look has made it possible the critical analysis of the gender questions and the anthropological background allowed a different look upon the ethnographic elements that the field has brought. The three articulated looks allowed the perception of dichotomies connected to gender, as the subversions to the orientations from Matta and Silva in the practice from the place.